Caracterización morfológica de la Tagua (Phytelephas macrocarpa) en el bosque húmedo de La Maná - Tonato Espín, Geovanny Ismael (2017)
The present research project was carried out at the Cotopaxi province on three bioclimatic grounds, those are in the Evergreen Forest low and evergreen seasonal mountain of the Western Mountain range of the Andes. It was divided into three altitudinal zones (high, medium and low), ranging from 300 m.o.s.l to 3.100 m.o.s.l The objective of the project was to perform the morphological characterization of the forest species Tagua (Phytelephas macrocarpa) by using qualitative and quantitative traits. The area was recognized on-site and with the helping of a GPS, georeferenced the area, delimiting the altitudinal zones. The presence of individuals on the three altitudinal zones was identified by the verification of the distribution of the Tagua species, this was useful to know the species density population. After identifying the distribution of the species, samples of the Tagua (Phytelephas macrocarpa) were collected, for which 20 individuals were selected for each altitudinal zones, , which allowed to obtain a characterization homogeneous. For the morphological characterization of the species, 18 qualitative descriptors were used, to which a statistical analysis was performed, and six quantitative descriptors were used, to which it statistical analysis of data was made, an analysis of main components for searching the existence of morphological variability. Key words: Humid forest, altitudinal zones, morphological descriptors, morphological variability.